1994
DOI: 10.1016/0020-0255(94)90040-x
|View full text |Cite
|
Sign up to set email alerts
|

B-trees with lazy parent split

Abstract: A B-tree variant that postpones parent node splittings due to upcoming items until a later access of the same node is examined. This technique aims to decrease the possibility of propagating splittings to upper levels so that more concurrency is achieved. Insertion and deletion algorithms are given. Time and space performance results are also reported and comparison with conventional B-trees is carried out. It is shown that this technique substantially improves the performance of small degree B-trees so that, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The lps technique is used to decrease the number of node splits during an insert operation; therefore, the number of locks is decreased and as a consequence enhanced concurrency is achieved. It has been shown that B-trees with lps achieve better storage performance [6]. However, a theoretical proof of this remark was lacking from the literature.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The lps technique is used to decrease the number of node splits during an insert operation; therefore, the number of locks is decreased and as a consequence enhanced concurrency is achieved. It has been shown that B-trees with lps achieve better storage performance [6]. However, a theoretical proof of this remark was lacking from the literature.…”
Section: Introductionmentioning
confidence: 91%
“…In [6] insertion and deletion algorithms have been given. When inserting a new key into a node containing less than 2d keys, it is placed among the other keys.…”
Section: B-trees With Lazy Parent Splitmentioning
confidence: 99%
See 1 more Smart Citation
“…Our construction is based on the use of a B-tree variant, which is called Lazy B-tree and has better dynamic performance as well as optimal I/O complexities for both searching and update operations [19]. An orthogonal effort towards developing yet another B-tree variant under the same name has been proposed in [24]. The Lazy B-tree of [19] is a simple but non-trivial externalization of the techniques introduced in [31].…”
Section: Handling Polygon Queries When Using the Hough-y Transformmentioning
confidence: 99%
“…Our construction is based on the use of a Btree variant, which is called Lazy B-tree and has better dynamic performance as well as optimal I/O complexities for both searching and update operations [15]. An orthogonal effort towards developing another yet B-tree variant under the same name has been proposed in [20]. The Lazy B-tree of [15] is a simple but non-trivial externalization of the techniques introduced in [24].…”
Section: Handling Polygon Queries When Using the Hough-y Transformmentioning
confidence: 99%